(untitled) (Journal of Organizational Psychology, 2022)
Frequent changes in commerce, economy, technology, finance, and regulations demand from organizations arrangements that may trigger inner disruptive effects if employees do not identify its meaning and coherence. Therefore, coherence is becoming relevant in psychology, organizational theory, and management. The current research aims to define a conceptual framework to examine coherence perceptions in organizational settings and develop a psychometric instrument to assess them. With a sample of 2053 employees from companies in Spain, Mexico, and Colombia, and through confirmatory factor analysis, we found, according to hypotheses, a four factors model with good fit indexes. There was no convincing evidence of factorial invariance because a few items promoted this condition, although they may be modified to tune up the measure in each country. This conceptual approach and the instrument designed are novel options for looking into perceived organizational coherence.